Species Diversity of Genus Aspergillus, Endophytic Fungal Isolated From Mangrove Ceriops tagal and their Antibiotic Potential - Sophia, Anggun; Agustien, Anthoni; Chairul; Syamsuardi (HAYATI Journal of Biosciences, 2025)
The rapid increase in antimicrobial resistance has encouraged development of new natural and urgent strategies to fight drug-resistant pathogens, one of which is using endophytic fungi. Endophytic fungi found in Ceriops tagal mangrove plant, which can adapt to extreme salinity environments of up to 60 ppt. Endophytic fungi are isolated from leaves, branch, and roots. Each isolate was identified morphologically and cultured in potato dextrose broth media for 21 days. After incubation, liquid culture was extracted with ethyl acetate and evaporated to obtain a thick extract. The Kirby Bauer method was used to evaluate the antibiotic potential of each endophytic fungal extract against pathogenic microbes Staphylococcus aureus, Escherichia coli, and Candida albicans. Concentration used was 5%, antibiotics used as positive controls were chloramphenicol (30μg/disk), nystatin (100 IU/disk), as negative controls DMSO. Three endophytic fungi were isolated from roots (ECT7, ECT 8, ECT 10), two from leaves (ECT 26, ECT 28) and six from branches (ECT 31, ECT 47, ECT 48, ECT 51, ECT 55 and ECT 85). Fungal isolates ECT10 has been proven to effectively exhibit strong antibiotic activity against microorganisms E. coli, S. aureus, and C. albicans, with inhibition zones measuring 13.0 mm, 11.8 mm, and 11.6 mm, respectively.